2018
DOI: 10.3390/su10113957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Using Task-Driven Classroom Teaching on Students’ Learning Attitudes and Learning Effectiveness in an Information Technology Course

Abstract: The Internet era of the modern day means that information technology no longer depends on computer theory. Instead, new education methods are used for innovative application. Therefore, the task-driven classroom teaching method is integrated into information technology teaching of junior middle school by designing specific cases. From the theoretical knowledge teaching and the comprehensive operational practice teaching, we explore the effect of using the task-driven classroom learning method on students’ lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Teacher questioning is one the most frequently used and significant ways of orchestrating students' thinking and reasoning [7]. A better documentation and fine-grained analysis of teacher questioning practices could help to understand how classroom interaction could be initiated and sustained, which thereby contributes to the construction of the desirable environment for constructive and rich classroom talk and to the cultivation of positive learning attitudes [36].…”
Section: Discussionmentioning
confidence: 99%
“…Teacher questioning is one the most frequently used and significant ways of orchestrating students' thinking and reasoning [7]. A better documentation and fine-grained analysis of teacher questioning practices could help to understand how classroom interaction could be initiated and sustained, which thereby contributes to the construction of the desirable environment for constructive and rich classroom talk and to the cultivation of positive learning attitudes [36].…”
Section: Discussionmentioning
confidence: 99%
“…There is a vast literature documenting the relationship between classroom climate and knowledge of student cognition at the primary school level (Fischer et al, 2018), secondary school level (Erdogan, 2019;Liu & Su, 2018;Zepeda et al, 2018) as well as the higher institutional level (Mccleary et al, 2019;Salam et al, 2020;Sugiharto et al, 2018). Further, recent empirical studies have confirmed there is a positive relationship between metacognition and achievement in many subject areas, such as science subject (Ellah et al, 2018;Langdon et al, 2019), mathematics subject (Bishara & Kaplan, 2018;Nurulhuda & Saemah Rahman, 2017;Riyan Hidayat et al, 2018;Al-Shabibi & Alkharusi, 2018) and language subject (Ghaith & El-Sanyoura, 2019).…”
Section: Mediation Effect Of Knowledge Of Cognition In Classroom Clim...mentioning
confidence: 99%
“…Extensive of studies revealed important findings related to classroom climate and regulation cognition (Alzahrani, 2017;Cayubit, 2021;Fathi & Shabani, 2020;Fischer et al, 2018;Hafızoglu & Yerdelen, 2019;Liu & Su, 2018) which have received adequate attention from the researchers and practitioners. Moreover, it should be noted that regulation cognition has been widely recognised as a potential predictor of the students' achievement (Izzati & Mahmudi, 2018;Mirhosseini et al, 2018;Mohamad Ariffin & Norulhuda, 2020).…”
Section: Mediation Effect Of Regulation Cognition In Classroom Climat...mentioning
confidence: 99%
“…Liu et al reported "Effects of Using Task-Driven Classroom Teaching on Students' Learning Attitudes and Learning Effectiveness in an Information Technology Course" [28]. From the theoretical knowledge teaching and the comprehensive operational practice teaching, the authors explore the effect of using the task-driven classroom learning method on students' learning attitudes and learning effectiveness in an information technology course.…”
Section: Tu Et Al Reported "Key Factors Of Sustainability For Smartpmentioning
confidence: 99%